Enforcement Against Extraordinary Members (ALB) of Notaries Who Violate the Notary Code of Ethics - Rahmawati, Nur Ainiyah; Sulistiyono, Adi; Hermawan, Sapto (Universitas Islam Sultan Agung, 2025)
The Notary Code of Ethics is a set of rules that are enforced and obeyed by notaries, used as guidelines for all notaries regarding what they should do, and at the same time guarantee the quality of notaries' conduct in the eyes of the public. Notaries who violate the provisions of the code of ethics will damage the reputation of the notary profession in the eyes of the public. The Indonesian Notary Association (INI) has three types of members: Regular Members, Extraordinary Members, and Honorary Members. To become a member of the INI association, prospective notaries must meet the requirements of a bachelor's degree in Law and a Notary Education/Specialized Notary Education diploma, and have passed the ALB selection process conducted by the INI as an official member of the INI organization. Once they have passed the ALB Notary exam and become members of INI, ALB Notaries must undergo an internship at a Notary office with the requirement of having served as a Notary for a minimum of 5 (five) years and having drafted at least 100 (one hundred) deeds. The internship must be completed as a prospective Notary for a consecutive period of 24 (twenty-four) months. During the internship period, the ALB Notary must already adhere to the Notary Code of Ethics since they are already a member of the INI organization. However, under the provisions of the Notary Code of Ethics, the ALB Notary is not included among those required to comply with the Notary Code of Ethics. The Notary Code of Ethics is only mandatory for those who have already assumed the position of Notary. Therefore, there is still a legal loophole for ALB Notaries if they engage in actions that violate the Notary Code of Ethics. The author used normative legal research in this study. A legislative approach and a conceptual approach were used in this study. The purpose of this study is to analyze and understand the handling of ALB Notaries who violate the Notary Code of Ethics.